2021
DOI: 10.3389/fped.2020.564902
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Fluid Content (TFC) Measurement Using Impedance Cardiography Predicts Outcomes in Critically Ill Children

Abstract: Objective: Conventional methods of fluid assessment in critically ill children are difficult and/or inaccurate. Impedance cardiography has capability of measuring thoracic fluid content (TFC). There is an insufficient literature reporting correlation between TFC and conventional methods of fluid balance and whether TFC predicts outcomes in critically ill children. We hypothesized that TFC correlates with indices of fluid balance [FIMO (Fluid Intake Minus Output) and AFIMO (Adjusted Fluid Intake Minus Output)] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This is in agreement with Sumbel et al who found that TFC correlated with findings of pulmonary plethora on chest X-ray. 20 Our study showed that TFC at 24 hours of 24 mL/kg and TFC drop rate at 24 hours of >12% are significant discriminators of TTN from non-TTN, with the sensitivity of 97.1 and 47.1% and specificity 60 and 82.4% respectively. However, no significant difference in the fluid balance was detected between the two groups with RD.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…This is in agreement with Sumbel et al who found that TFC correlated with findings of pulmonary plethora on chest X-ray. 20 Our study showed that TFC at 24 hours of 24 mL/kg and TFC drop rate at 24 hours of >12% are significant discriminators of TTN from non-TTN, with the sensitivity of 97.1 and 47.1% and specificity 60 and 82.4% respectively. However, no significant difference in the fluid balance was detected between the two groups with RD.…”
Section: Discussionmentioning
confidence: 50%
“…This is in agreement with Sumbel et al who found that TFC correlated with findings of pulmonary plethora on chest X-ray. 20…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic intravascular and extravascular fluid content affect TFC values that are calculated from the thoracic electrical bioimpedance. Variations in TFC are known to reflect the total fluid changes [ 49 , 50 ]. In our study dogs, we find the TFC values closely follows the changes in the CO PATD such that they decrease with hemorrhage and normalize to baseline values after autologous blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed a significant decrease in RR, MAP, SVR, and STR and an increase in TFC, while CO, CI, SV, and SI remained unchanged. TFC is a newer objective parameter that has shown to identify pulmonary congestion which might not be evident on chest x-rays ( 36 , 37 ). One study in critically ill children with respiratory failure and shock demonstrated that high TFC values correlate with pulmonary plethora and predicted patient outcomes ( 37 ).…”
Section: Discussionmentioning
confidence: 99%